Berguño Hurtado, Fernando. Los soldados de Napoleón en la independencia de Chile. 1817- 1830. Santiago: RIL Editores. 2015. 343 páginas. ISBN 978-956-01-0203-4. - Orellana Billiard, Jorge Andrés (2018)
Fil: Orellana Billiard, Jorge Andrés. Universidad Diego Portales (Santiago, Chile)